Efficacy of tank mixtures of post-emergence herbicides in common bean - Costa, Júlia Carvalho; Moreira, Silvino Guimarães; Carvalho, Antonio Henrique Fonseca de; Pimentel, Guilherme Vieira; Torres, Diego Rafael Quispe; Silva, Junior Cézar Resende (Revista Agrogeoambiental, 2021)
In common bean, the occurrence of weeds can cause significant reductions in the final grain yield. This study aimed to evaluate the efficiency of different herbicide trials, applied individually or in a mixture, in the management of common bean weeds. A randomized complete block was used, arranged in subdivided plots. The main plots consisted of three types of beans (Carioca Pérola cultivar, Black cultivar IPR Tuiuiu and one Red Bean strain VR20) and the subplots of different control modes, in four replications: hand weeding, fomesafen (250 g per hectare of ingredient active (g ha-1 of a.i.)), fomesafen (375 g ha-1 of a.i.), imazamox + bentazon (0,23 + 0,6g ha-1 of a.i.), imazamox + bentazon + fomesafen (0.23 + 0.6 + 125 g ha-1 of a.i.) and imazamox + bentazon + fomesafen (0.23 + 0.6 + 83 g ha-1 of a.i.). The following traits were evaluated during three seasons: weeds present in the area, phytotoxicity symptoms, and common bean grain yield. The data were analyzed using a variance analysis (F test), the means obtained were grouped by the Scott Knott test at 5 % probability. Differences in grain yield performance were observed between cultivars and crops season due to herbicide application. The most efficacy treatment for weeds was imazamox + bentazon + fomesafen (230 + 600 + 125 g ha-1 of a.i.), resulting in improved control and greater efficiency in avoiding grain yield losses.